Investigation on The Awareness and Perception, Attitude, and Implementation of The Concept of Islamization of Knowledge Among University Educators - Fazlinda Hamzah, Mohd Azlan Shah Sharifudin (Universiti Sains Islam Malaysia, 2017)
This paper attempts to shed some light on the extent to which university educators who are Muslim by religion familiarize themselves with the concept of Islamization of knowledge in their teaching. It is generally argued that knowledge is free from any intrinsic values that may render it biased toward a culture or religious tradition (Bashir, 2000). However, Muslim scholars such as Ismail Al-Faruqi and Syed Naquib Al-Attas refuted such claim as they believe such perception would put Muslim students at risk of being helpless against the onslaught of scientific truth. Survey research design was employed to execute this investigation in which a number of educators from various fields offered in UiTM Melaka were selected to answer 11 questions related to their awareness and perception, attitude, and implementation of Islamization of knowledge. General overview from the results revealed a rather promising outlook to the prior assumption that educators are oblivious towards the concept of Islamization of knowledge.